PERANCANGAN SIMULASI COUNTDOWN TIMER PADA ALAT KESEHATAN BERBASIS ARDUINO UNO DAN SIMULASI WOKWI - mahardhika, Pramudya; Haris Kuspranoto, Abdul (MEDIKA TRADA : Jurnal Teknik Elektomedik Polbitrada, 2024)
A countdown timer is a device or function in software that is designed to count down time from a starting point until it reaches zero. Its function is simple, namely to provide a visual or auditory indication of the remaining time remaining before a certain event or time limit is reached. The countdown timer implemented in this health device aims to provide clear time warnings to users regarding certain times related to health monitoring. For example, when using inhalers for asthma patients, a countdown timer can provide a countdown warning before the next inhalation, helping patients to follow the medication schedule more regularly. In this Countdown Timer series, we use an Arduino Uno manager to display it on the I2C 2x16 Liquid Crystal Display (LCD) and various other components. By implementing logic methods for countdown timers and alarms when the time reaches zero, it can provide an effective and efficient solution for monitoring critical time in various health applications, such as the use of inhaler medication for asthma patients. Further implementations may include integration with an RTC module for better timing accuracy and the use of additional sensors for more complex functions.